Global Perspectives in Policing and Law Enforcement - Mbuba, Jospeter M. (Lanham: Lexington Books, 2021)
"This book provides an exposition of policing and law enforcement practices, challenges, and opportunities in twenty different countries that were carefully selected to represent diverse geographic regions of the world. Each chapter presents policing from a different cultural background with diverse historical law enforcement experiences, varied social and demographic characteristics, and wide-ranging approaches to political leadership. By examining critical data and highlighting cracks within law enforcement across multiple countries, the contributors to this volume have created a framework of policing as it transitions into a modern outfit. Divided into parts, the book focuses on a large sample of countries from Africa, Europe, Asia, and Latin and Central America, North America and the Caribbean, as well as Australia and New Zealand"--Provided by the publisher.
Includes bibliographical references and index (pages 367-377).
Keywords: Police; Law enforcement; Law enforcement; Police